Answer:
L' = (2, -2)
M' = (0, -3)
Explanation:
Let us revise the rules of translation
- If the point (x, y) translated horizontally to the right by h units then its image is (x + h, y) ⇒ T (x, y) → (x + h, y)
- If the point (x, y) translated horizontally to the left by h units then its image is (x - h, y) ⇒ T (x, y) → (x - h, y)
- If the point (x, y) translated vertically up by k units then its image is (x, y + k)→ (x + h, y) ⇒ T (x, y) → (x, y + k)
- If the point (x, y) translated vertically down by k units then its image is (x, y - k) ⇒ T (x, y) → (x, y - k)
∵ Point L is (0, 1)
∵ L translated 2 units right and 3 units down
→ By using the 1st and 4th rules above, add its x-coordinate by 2
and subtract its y-coordinates by 3
∴ The rule of translation is T (x, y) → (x + 2, y - 3)
∴ L' = (0 + 2, 1 - 3)
∴ L' = (2, -2)
∵ Point M is (1, -2)
∵ M' = (x - 1, y - 1)
→ By using the 2nd and 4th rules above, it is translated 1 unit left and
1 unit down
∴ M' = (1 - 1, -2 - 1)
∴ M' = (0, -3)